ANALISIS BUTIR SOAL UJIAN SEMESTER GENAP KELAS XI IPA SMA NEGERI 1 PERANAP TAHUN AJARAN 2013/2014 - Rahmadeni, Deta Marlia; Thaib, Armiyus; ', Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrack: This research is an ex post facto, meaning that the data collected after all the events that happened note. This study aims to determine the quality of the best items semester chemical subjects exam. The sample in this study is the second semester exam of class XI IPA SMA N 1 Peranap academic year 2013/2014. The variables measured in this study a qualitative analysis,the level of difficulty, distinguishing features, functions distractor, validity and realibility. Based on the results of analysis show that about qualitative term is 18 rejected, 8 matter retified, 14 received . While quantitative terms, the level of difficulty, distinguishing is less, and distractor function is less proportionately too, but of validity is sufficient . Only the value r11 = 0,6, indicating that this matter has not been reliable. Semester exam class XI IPA SMA N 1 Peranap needs a lot of improvement both in terms qualitatife or quantitative.Keywords : analysis, qualitative, quantitative, distractor, validity, realibility.